Radioimmunoassay for choline acetyltransferase - LING Shi-gan; BAO Zhong-qi; LI Ling; WANG Guang-yuan (Acta Pharmacologica Sinica, 2016)
A simple radioimmunoassay for determination of choline-o-acetyltransferase(ChAT) activity is reported. 0.4mM of acetylcoenzyme as the substrates. Because the antiserum is specific for Ach, CHAT activity of reaction mixture was detected directly without separating the enzymatic product Ach from the substrates. ChAT activities of 0.5 mg of mouse brain and diaphragm measured by this method were 45±6 and 3.0±0.4 pmol Ach/min/mg, respectively. When the mice were injicted ip with 4-(α-naphthylvinyl) pyridinium (NVP, 200 mg/kg), the activity of ChAT was inhibited by 73%, but there was no effect on the content of Ach. Owing to the specificity, simplicity and sensitivity, this radioimmunoassay is a good substitute for radiochemical method.